Entrepreneurial leadership: shooting for the stars / Rohana Ngah ... [et al.] - Ngah, Rohana; Salleh, Zarina; Sarmidy, Rahimah; Othman, Hamizah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Entrepreneurial leadership is vital to ensure the sustainability and growth of any organization. This case study presents the challenges faced by a small company in sustaining its competitive advantage and supporting its target growth. Being small has its advantages, as a small organization is said to have an excellent platform to develop talents for succession. The founder and owner had started his succession program by providing staff training. The staff also were given opportunities to lead projects with close supervision. However, the company is struggling to grow due to a lack of competent employees to support its growth mission. As the driver of the company, Azlan felt that he had provided opportunities to his employees to improve themselves, but their competencies are still below Azlan's expectations. Based on the innovation audit, overall, the company is on an excellent track. The company capitalizes on its strengths in linkages, learning, and process; however, it needs to improve its strategy and innovation. The future of the company is in the hand of its people.